ChemInform Abstract: Convergent Access to Bis‐Spiroacetals Through a Sila‐Stetter—Ketalization Cascade. Issue 4 (28th January 2014) - Labarre‐Laine, Jessica; Beniazza, Redouane; Desvergnes, Valerie; Landais, Yannick
Abstract The NHC‐catalyzed title reaction between aliphatic acylsilanes and vinylketones bearing silyl ether groups affords bis‐spiroacetals (IV) and (XV) in two steps.